2014
DOI: 10.1007/s12678-014-0230-1
|View full text |Cite
|
Sign up to set email alerts
|

Using the Alkynyl-Substituted Rhenium(I) Complex (4,4′-Bisphenyl-Ethynyl-2,2′-Bipyridyl)Re(CO)3Cl as Catalyst for CO2 Reduction—Synthesis, Characterization, and Application

Abstract: The synthesis, structure, photophysics, and spectroscopic characterization of an organometallic rhenium multichromophore compound carrying a central 2,2′-bipyridyl acceptor moiety with additional phenylethynyl substituents conjugated at the 4,4′-positions of the acceptor ligands and its effect on the electron density of the central rhenium atom as metal center for CO 2 reduction is reported. The results were compared to fac-(2,2′-bipyridyl)Re(CO) 3 Cl and fac-(5,5′-bisphenylethynyl-2,2′-bipyridyl)Re(CO) 3 Cl. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Despite this, continuing research efforts to produce commercially viable functionalization of CO 2 remains some distance away . Currently, much of the literature regarding molecular electrochemical activation of CO 2 still continues to explore the catalytic properties of the heavier members of Group‐7 (Re), Group‐8 (Ru and Os) and Group‐9 (Rh, and Ir) triads. These “first‐generation” electrocatalysts must be phased out; encouragingly, cheaper alternatives exist within the same groups – Mn substituting Re, Fe substituting Ru and Os, and Co substituting Rh and Ir .…”
Section: Methodsmentioning
confidence: 99%
“…Despite this, continuing research efforts to produce commercially viable functionalization of CO 2 remains some distance away . Currently, much of the literature regarding molecular electrochemical activation of CO 2 still continues to explore the catalytic properties of the heavier members of Group‐7 (Re), Group‐8 (Ru and Os) and Group‐9 (Rh, and Ir) triads. These “first‐generation” electrocatalysts must be phased out; encouragingly, cheaper alternatives exist within the same groups – Mn substituting Re, Fe substituting Ru and Os, and Co substituting Rh and Ir .…”
Section: Methodsmentioning
confidence: 99%
“…1A); in these cases, the absorption is red-shifted due to a stabilization of the ligand-centred π * orbitals (typically the LUMO). 22 While the effects of substitution in the vicinity of the metal centre have been previously described for Re(I) tricarbonyl complexes, [23][24][25][26] further understanding of the effects of substitution far away from the metal centre (Fig. 1B) is needed, and constitutes a promising alternative to fine tune the properties of these complexes.…”
Section: Introductionmentioning
confidence: 94%
“…Portenkirchner et al made ac omparatives tudy and investigated the differences in catalytic activity arising from the same group substituted at different positions (compounds 6 and 7, Figure7). [29] The authors once again showed the effect of extended p-conjugation on the absorption characteristics ( Figure 8) noting that this can have an impact on photocatalytic properties. Rotating-disce lectrode measurements in this study showed that the diffusion coefficient of 7 was 2.5 10 À6 cm 2 s À1 ,w hich was in good agreementw ith earlierl iterature values.…”
Section: Rhenium-and Manganese-containing Organometallic Complexesmentioning
confidence: 89%
“…alytic rate dropped drastically to 30 m À1 s À1 .T his difference was attributed to the availability of activated protons on the Pt electrode. [29] Althoughv ariousm olecular catalysts (porphyrins, corroles, cyclams,n aphthyridines, and so forth) with metal centers such as Pd, Ru, Fe, Co, and Ni were investigated, [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] in the years after the discovery of Lehn'sc atalyst, most research has been focusedo nR e-containing complexes. With an estimated average concentration of 1ppb, Re, together with other noble metals,i so ne of the rarest elements in Earth's crust.…”
Section: Rhenium-and Manganese-containing Organometallic Complexesmentioning
confidence: 99%